1988
DOI: 10.1021/bi00406a012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a human .alpha.-tubulin: properties of the isolated subunit

Abstract: We examined the in vitro expression and biochemical properties of the isolated alpha subunit of tubulin both in rabbit reticulocyte lysates and in Escherichia coli extracts. Both systems produce soluble, full-length human alpha-tubulin polypeptide. When alpha-tubulin mRNA is translated in rabbit reticulocyte lysates, the isolated alpha subunit is fully functional as assayed by coassembly with bovine brain tubulin using temperature-dependent or taxol/salt assembly procedures. The conformation of the isolated al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…Therefore, it seems reasonable that de novo synthesized a-tubulin might exchange within the heterodimer pool, and thus become dimer (mouse a-rabbit P). Because in vitro synthesized a-tubulin is indistinguishable in size, charge and polymerization properties from dimers [Yaffe et al, 1988b; and this work], we believe that this species represents tubulin dimer.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, it seems reasonable that de novo synthesized a-tubulin might exchange within the heterodimer pool, and thus become dimer (mouse a-rabbit P). Because in vitro synthesized a-tubulin is indistinguishable in size, charge and polymerization properties from dimers [Yaffe et al, 1988b; and this work], we believe that this species represents tubulin dimer.…”
Section: Discussionmentioning
confidence: 70%
“…Also, we could not detect the presence of a-tubulin monomers even at early times after a kinetic analysis of de novo synthesis of different a-tubulin isotypes. Yaffe et al [1988b] suggested that the in vitro synthesis of a-tubulin generates monomeric subunits but not dimeric forms. This conclusion was based on the observation that the a-tubulin product could not be immunoprecipitated with a P-tubulin monoclonal antibody and that its protease digestion pattern differed from that of cycled, translated a-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…1C, lanes 7 and 12). In contrast, the translation of mRNAs encoding either a-or ,B-tubulin in unfractionated rabbit reticulocyte lysate leads to the synthesis of assembly-competent tubulin (6,51). These data led us to suspect that some factor or factors in addition to chaperonin itself must be required for the proper folding of a-and 13-tubulin.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that while the idea that et-tubulin represses its own synthesis is consistent with the data, we cannot presently rule out the possibility that 13-tubulin, alone or in combination with some other factor, binds to et-tubulin m R N A and directly promotes translation. However, there is currently little evidence for this type of translational control, except in viral systems (Standart and Jackson, 1994), and the fact that et-tubulin can be successfully translated in vitro in the absence of new 13-tubulin synthesis (Yaffe et al, 1988) leads us to prefer a mechanism in which et-tubulin acts as a repressor of its own translation. Whatever the actual mechanism, our results suggest that a-tubulin synthesis is controlled by the availability of [3-tubulin for heterodimer formation.…”
Section: Discussionmentioning
confidence: 99%